FACTOR INFLUENCING THE DECISION TO PURCHASE SUKUK MUDHARABAH PRODUCTS IN THE COMMUNITY - Muhammad R.H, Syanaiskara; Devi, Abrista; Ikhtiono, Gunawan (Al-Mubin, 2025)
One way to build a nation is the economy and see how far the development of Islamic Finance has gone. Sukuk Mudharabah is an attractive sharia investment instrument, but people's interest is still influenced by several factors such as financial literacy, understanding of benefits, motivation, minimum capital, and risk preferences. Sukuk is not only a debt document like a bond, but sukuk is a debt document that is based on sharia law as a rule and based on the company's tangible assets as guarantor. This study was conducted with the aim of determining the influence of Literacy, Benefits, Motivation, Minimum Capital, and Risk Preferences on the purchase decision of Sukuk Mudharabah Product in the Jabodetabek area. This research method uses a quantitative approach. The population in this study is the community in the Jabodetabek area. The research sample used was 115 respondents using random sampling techniques. The data analysis technique uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) method through SmartPLS 4.0 software. The results of the study show that Literacy, Benefits, Minimum Capital, and Risk Preferences have a significant and positive effect on the Purchase Decision of Sukuk Mudharabah Product. Meanwhile, Motivation did not have a significant and positive effect on the Decision to Purchase Sukuk Mudharabah Product